The Role of English-Language Entertainment Exposure in Developing English Reading Comprehension Skill - Gesta, Raponzel; Paguya, Fresy Mae; Quiño-Justol, Jeddah (Journal of Interdisciplinary Perspectives, 2025)
Reading comprehension remains a pressing challenge in Philippine education, as reflected in the country’s low performance in the 2018 Programme for International Student Assessment (PISA). While English-language entertainment, particularly video content and music, has become deeply embedded in students’ daily routines, its contribution to academic reading skills remains underexamined. This study explored the relationship between English-language entertainment exposure and reading comprehension among 117 first-year Bachelor of Secondary Education (BSED) English students at Tagoloan Community College. Using a descriptive-quantitative research design and a census sampling method, data were gathered through a validated researcher-made questionnaire with a high content validity index (CVI = 0.95). Findings revealed that students engaged with English-language video and music content on a “daily or almost daily” basis (composite means: video = 3.25; music = 3.36). However, despite this frequent exposure, their average reading comprehension score was only 9.85 (SD = 2.50), placing most students in the “Proficient” and “Developing” categories. Spearman’s Rank Correlation indicated no significant relationship between exposure to video content (ρ = 0.057, p = 0.543) or music content (ρ = 0.080, p = 0.390) and reading comprehension scores. These findings suggest that while English-language entertainment may support general language familiarity, it is insufficient on its own to improve reading comprehension. The study underscores the importance of integrating media content into explicit literacy instruction and structured reading interventions. Future research may adopt experimental or mixed-method designs to investigate mediating variables such as digital literacy, reading motivation, or strategy use, and to understand better how entertainment media can be leveraged for instructional gain.